La devoción del salvaje. Religiosidad zapatista y silencio gráfico - Ariel Arnal (L'Ordinaire des Amériques)
During the official period of the Mexican Revolution, 1910 – 1919, the armed movement headed by Emiliano Zapata was a permanent subject for photographers working for the Press in Mexico City. Except for the short period of the Conventionist Government in the Capital City (1915), photography was repeatedly used to denigrate the Southern Army. This was opposed to the traditional values of nationalism, religion, and family. Nevertheless, during the above-mentioned period, there is a topic that was never broached: the use of religious symbols by the “surianos” (Southern Army). On the other hand, countless photographs have been found in the archives that document the deep religious feeling among the Zapatista Army and its “caudillos” (leaders). From this point of view, the use of religious symbols by the rebels as well as the omission of this valuable information by the Press in Mexico City tell us about the building of an editorial discourse that is paradoxically supported by silence, a silence that becomes a truly dramatic actor and can be considered as profoundly eloquent.